PENGARUH PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE TWO STAY TWO STRAY (TS-TS) TERHADAP HASIL BELAJAR IPS TERPADU SISWA KELAS VIII - Supriatin, Endang; Wakijo, Wakijo (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
Education is a very important element to create a quality resource, intelligent, open peace, democratic, and able to compete and can improve the welfare of all Indonesian citizens. The state is said to be advanced in all fields whether in the field of economics, technology, agriculture or the other cannot be separated from the role of education. But in reality both in the process and the results of learning are still many that have not been in accordance with expectations in educational goals, it is also seen in the learning outcomes in SMP Negeri 6 Metro class VIII still many students learning outcomes that have not reached the minimum mastery criteria (KKM). The result of study that has not been completed is 21 students with 65,63% percentage, and that reaching completeness learn is 11 students with percentage 34,37%, while the minimum grade (KKM) Grade VIII SMP 6 Metro in Integrated IPS lesson is 75. Alternatives to improve studentlearning outcomes are used Influence Cooperative Learning Model Type Two Stay Two Stray (TS-TS). The purpose of this research is to know the Influence of Cooperative Learning Model Type Two Stay Two Stray (TS-TS) on Learning Outcomes Integrated IPS Students Class VIII Even Semester SMP Negeri 6 Metro academic year 2017/2018. The population in this study consists of 8 classes and total of students is 250. Samples were taken by technique of sampling and obtained class VIII 5 which amounted to 32 students as a class which used as experiment or class research which got treatment using Two Stay Two Stray Model Cooperative Learning (TS-TS). After analyzed data of research the result can be concluded that from calculation analysis tcount > ttable. It can be seen on the list of G, at a significant level of 5% that is 3.40> 1.70 and at a significant level of 1% that is 3.40> 2.46. Thus the hypothesis reads that there is a positive influence of the use of Cooperative Learning Model Type Two Stay Two Stray (TS-TS) can improve the learning outcomes of IPS student class VIII even Semester of SMP N 6 Metro. Students who declared complete with KKM 75 after given treatment as many as 27 students or equal to 84,37% and student whichexpressed not yet completed as many as 5 students or equal to 15,63%, hence the process of learning say succeed.